Euphemisms Related To Certain Vices Between The Individual And Society - Sirojiddin Turdimurodov (International Scientific and Current Research Conferences, 2021)
Euphemisms are a multifaceted and widespread phenomenon, it is used not only instead of taboo words, but also for mild expression of the meaning of units that are inconvenient to pronounce. The article provides a comparative, lexicographic analysis of the role of lexical units in the explanatory dictionaries of the Uzbek language, which are euphemistic in nature, associated with certain defects between the individual and society.